MEMBANGUN RELASI HARMONIS ANTARA KRISTIANI DAN ISLAM: Kajian Kristus dan Isa Almasih - Akwila, Akwila; Tinenti, Hemma Gregorius (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
This research was conducted based on the author's explanation of the situation that has occurred recently. There are certain elements who use certain religions and attack the doctrines of other religious beliefs. So through this study the author wants to build constructive communication and dialogue without conflict. The study only focuses on Christian and Islamic views on the figure of Christ (Isa the Messiah). This study is also linked to the call for peace made by Pope Francis in the Fratelli Tutti Document and the Abu Dhabi Document. The method used by the author to dig up information is documentation study, where the author studies writings that discuss Jesus Christ from both Islamic and Catholic doctrines. In data analysis the author uses Pope Francis' documents to describe the harmonious relationship that must be built and Isa Almasih (Jesus Christ) as an example and role model. The author suggests that future researchers conduct similar research, but use different research methods and data collection. Future researchers are expected to use empirical study methods in which information is not only obtained theoretically but can also extract information from religious figures, both Islamic and Catholic, who have mastered the field of Christian science.